Food Safety Risk Analysis of Songkem Duck Using Failure Mode and Effect Analysis (FMEA) Method: Analisis Risiko Keamanan Pangan pada Bebek Songkem Menggunakan Metoda Failure Mode and Effect Analysis (FMEA) - Anisa, Mawadatun; Burhan, Burhan; Indarto, Cahyo (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2024)
Food safety is an essential aspect of human health. Food processed without paying attention to food safety regulations can harm consumer health. This research aims to 1) identify activities with food safety risks, 2) determine the sequence of food safety risks that will be followed up, and 3) determine appropriate food safety risk mitigation. This research uses the Failure Mode and Effect Analysis (FMEA) method and fishbone diagrams. A case study was conducted on the Songkem pak Soleh Bangkalan duck supply chain. The research results show that activities that pose a food safety risk include receiving raw materials, storing raw material stocks, using raw materials and BTP, sanitizing production facilities, and storing finished products. The priority order of food safety risks in the Songkem duck supply chain is based on the FMEA method: storage of finished products, sanitation of production facilities, and storage of raw material stocks. Risk mitigation can be done to prevent food safety risks in storing raw material stocks and storing finished products, namely by controlling water activity (aw) and acidity factor (pH); and controlling the room's atmosphere. Meanwhile, to prevent risks due to sanitation hygiene, namely holding training to increase awareness of the importance of sanitation hygiene for restaurant employees monitoring and maintaining sanitation hygiene in the production environment.